“The Enemy of the Good”: Reflections on Ireland’s New Abortion Legislation - Enright, Mairead (feminists@law, 2018)
This short reflection presents a personal account of the process and outcome, the achievements and disappointments of legislative reform following the Irish referendum to repeal the 8th Amendment to the Irish Constitution. While the new Health (Regulation of Termination of Pregnancy) Act 2018 will afford access to legal abortion to many women for the first time in Ireland, it does not meet feminist demands and is likely to exclude a range of women in difficult and marginalised circumstances. The piece reflects on the frustrations and compromises of feminist law reform and concludes that the process of abortion law reform in Ireland will be ongoing.